Manajemen Kurikulum Merdeka dalam Meningkatkan Motivasi Belajar Siswa di SD Negeri 2 Cibenda - Annisa Kania Fauzani Tarigan (J-STAF: Siddiq, Tabligh, Amanah, Fathonah, 2025)
Lack of interest and motivation in students' learning can lead to laziness during the learning process. This, of course, is a concern for educational institutions. This research aims to understand how the management of the Merdeka Curriculum can enhance student motivation at SDN 2 Cibenda. The Merdeka Curriculum is designed to provide schools with flexibility so they can adjust to their specific environment. The implementation of the Merdeka Curriculum is expected to boost students' motivation to become more creative and active in learning, aligned with their interests and talents. This study uses a qualitative method, with the subjects being the principal, teachers, and students. The research was conducted at SD Negeri 2 Cibenda. Data collection techniques included observation, interviews, and documentation conducted directly in the field. The data analysis technique used involves data reduction, data presentation, and conclusion drawing. The research results conclude that the management of the Merdeka Curriculum can increase students' motivation at SD Negeri 2 Cibenda. The curriculum management process consists of several stages: curriculum planning, curriculum organization, curriculum implementation, curriculum evaluation, and curriculum development. Curriculum planning is carried out by fulfilling physiological needs, self-actualization, and social needs. Curriculum organization is achieved by meeting social needs and self-actualization needs. Curriculum implementation is carried out by fulfilling physiological needs, security and safety needs, social needs, esteem needs, and self-actualization needs. Curriculum evaluation focuses on meeting self-actualization needs, while curriculum development also focuses on fulfilling self-actualization needs.